A Phase 1 study of ADI‐PEG20 (pegargiminase) combined with cisplatin and pemetrexed in ASS1‐negative metastatic uveal melanoma. (16th May 2022) - Chan, Pui Ying; Phillips, Melissa M.; Ellis, Stephen; Johnston, Amanda; Feng, Xiaoxing; Arora, Amit; Hay, Gordon; Cohen, Victoria M. L.; Sagoo, Mandeep S.; Bomalaski, John S.; Sheaff, Michael T.; Szlosarek, Peter W.
Abstract: Metastatic uveal melanoma (UM) is a devastating disease with few treatment options. We evaluated the safety, tolerability and preliminary activity of arginine depletion using pegylated arginine deiminase ( ADI‐PEG20; pegargiminase) combined with pemetrexed (Pem) and cisplatin (Cis) chemotherapy in a phase 1 dose‐expansion study of patients with argininosuccinate synthetase (ASS1)‐deficient metastatic UM. Eligible patients received up to six cycles of Pem (500 mg/m 2 ) and Cis (75 mg/m 2 ) every 3 weeks plus weekly intramuscular ADI (36 mg/m 2 ), followed by maintenance ADI until progression (NCT02029690). Ten of fourteen ASS1‐deficient patients with UM liver metastases and a median of one line of prior immunotherapy received ADIPemCis. Only one ≥ grade 3 adverse event of febrile neutropenia was reported. Seven patients had stable disease with a median progression‐free survival of 3.0 months (range, 1.3–8.1) and a median overall survival of 11.5 months (range, 3.2–36.9). Despite anti‐ADI‐PEG20 antibody emergence, plasma arginine concentrations remained suppressed by 18 weeks with a reciprocal increase in plasma citrulline. Tumour rebiopsies at progression revealed ASS1 re‐expression as an escape mechanism. ADIPemCis was well tolerated with modest disease stabilisation in metastatic UM. Further investigation of arginine deprivation is indicated in UM including combinations with immune checkpoint blockade and additional anti‐metabolite strategies.